2019
DOI: 10.20355/jcie29354
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Thinking I Want to Live a Better Life”: Syrian Refugee Student Adjustment in New Brunswick

Abstract: In this paper, the authors explore the re-adjustment experiences of seven refugee students from Syria and Iraq, who enrolled in a large high school in New Brunswick. Data were collected through semi-structured interviews, school and community documents, and field notes. Five themes were identified and are reported and discussed in this paper. Recommendations for future direction regarding how to successfully integrate Syrian refugee children into Canadian schools are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Further, we encourage school leaders to think deeply when they set up EAL programs for new Canadian students. We have found conclusively that newcomer and refugee students want Canadian friends (Massfeller & Hamm, 2019). Further, they are often marginalized and racialized by some of their Canadian peers, either overtly or covertly.…”
Section: Confront Conflict and Engage In Critical Dialoguementioning
confidence: 67%
See 2 more Smart Citations
“…Further, we encourage school leaders to think deeply when they set up EAL programs for new Canadian students. We have found conclusively that newcomer and refugee students want Canadian friends (Massfeller & Hamm, 2019). Further, they are often marginalized and racialized by some of their Canadian peers, either overtly or covertly.…”
Section: Confront Conflict and Engage In Critical Dialoguementioning
confidence: 67%
“…Secondly, what are some effective responses that educators are providing for new Canadian students and their families, during and after their settlement and adjustment in New Brunswick? In our previous studies of New Brunswick, we found that educators experience various levels of stress and anxiety as they help new Canadian students adjust to their new schools and communities (Hamm, 2017;Hamm, Massfeller, Scott, & Cormier, 2017;Massfeller & Hamm, 2019). Still, the academic literature is limited on studies of immigration, demographic change, and diversity in New Brunswick.…”
Section: Immigration and The New Brunswick School Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, school staff and organizations played important roles in helping teenage Syrian refugees navigate their new lives in Canada by providing resources. The support of school staff, which included teachers and guidance counsellors, is important for helping refugee youth resettle and flourish academically (Massfeller & Hamm, 2019;Salam et al, 2022a). For many newcomers in Canada, resettlement organizations play an important role in helping provide vocational and language training (Shields et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Literature on Syrian refugee youth mental health connects resettlement experiences and stressors (Guo et al, 2019;Hanley et al, 2018;Massfeller & Hamm, 2019;Scharpf et al, 2021;Walker & Zuberi, 2019). However, a paucity of research examines coping strategies among this population, and therefore, further exploration may be helpful in understanding how to reduce negative mental health outcomes and promote positive well-being.…”
Section: Introductionmentioning
confidence: 99%